STRATEGI DAKWAH GERAKAN NURCU PADA MASA PEMERINTAHAN RECEP TAYYIP ERDOGAN - Mevy Eka Nurhalizah; Jamaluddin Syakirin (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This paper aims to describe the da’wa strategy of the Nurcu movement in the dynamics of ideologies in Turkey during Erdogan's reign, as well as its correlation with Al-Madkhal Ila Ilmi Dakwah's book by Al Bayanuni. The existence of the three ideologies that developed in Turkey, namely Islamism, western ideology, and nationalism, is still developing today. Various reforms and branches of each movement have colored the socio-political life in Turkey. One example of being part of a reformer is the Nurcu Movement, which is part of the Islamism group. This movement was led by Bediuzzaman Said Nursi with his monumental work entitled Risale-i Nur (Faiz, 2017). Said Nursi was one of the figures who initiated resistance to government policies during the Ataturk era. The resistance carried out by Nursi did not use weapons, but with a different da'wah strategy This paper is a literature study, with a historical analysis approach to the Nurcu Movement in Turkey through the work of other relevant researchers. The study results show that the da’wa strategy used by the Nurcu movement is persuasive, logic, and dialogue. In addition, the Nurcu movement also used three da’wa strategies according to Al-Bayanunni namely al-athifi, al-aqly, and al-hissi. This movement spread its da'wa by entering into five fields, namely social, journalist, media, education and economics. The preaching strategy of the Nurcu movement can be said to be successful because it is able to survive and continue to exist today.